2010
DOI: 10.3109/17453671003667176
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome of revised resurfacing hip arthroplasty

Abstract: Background and purposeRecent years have seen a rapid increase in the use of resurfacing hip arthroplasty despite the lack of literature on the long-term outcome. In particular, there is little evidence regarding the outcome of revisions of primary resurfacing. The purpose of this analysis was to examine the survivorship of primary resurfacing hip arthroplasties that have been revised.Patients and methodsOver 12,000 primary resurfacing hip arthroplasties were recorded by the Australian Orthopaedic Association N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 8 publications
3
53
1
Order By: Relevance
“…We are unaware of other published reports of complications after revision of these devices, although others have observed similar problems after revision of hip resurfacing [9,17]. The rate of dislocation in this study was 28% overall (nine of 32 hips).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…We are unaware of other published reports of complications after revision of these devices, although others have observed similar problems after revision of hip resurfacing [9,17]. The rate of dislocation in this study was 28% overall (nine of 32 hips).…”
Section: Discussioncontrasting
confidence: 43%
“…ALTRs can cause pain, damage to local bone and soft tissue, and instability of the prosthetic joint. Although high rates of complication and rerevision have been reported after revision of largehead MoM resurfacing devices [2,9,17], to our knowledge, there are no published reports of outcomes after revision of large-head, MoM THA. We therefore sought to determine (1) complications occurring after revision, including reoperations; (2) radiologic outcome; and (3) changes in metal ion levels after revision of the bearing to metal-on-polyethylene.…”
Section: Introductionmentioning
confidence: 69%
“…This was also studied by the previously mentioned AOANJRR paper [5], which reported that acetabular-only revision had a significantly higher risk of revision compared with femoral-only revision but not among the other groups (a 5-year cumulative percent revision rate of 20%, 7%, and 5%). Grammatopoulos et al [6] identified 53 hips in 51 patients that had undergone revision surgery after hip resurfacing arthroplasty, of which 16 were revised for pseudotumor formation.…”
Section: Discussionmentioning
confidence: 94%
“…Few other studies have investigated the longterm survivorship of revision for hip resurfacing arthroplasty. A previous study by the AOANJRR in 2010 [5] looked at the early rerevision rate of 397 revisions for reasons other than infection, finding a cumulative percent rerevision rate of 9% at 5 years. This current analysis has been performed on more than twice the number of revision procedures with a longer followup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation